Evaluation of the effect of stock enhancement in the coastal waters of Guangdong, China. (April 2015) - Chen, P.; Qin, C.; Yu, J.; Shu, L.; Li, X.; Zhou, Y.; Yuan, H.
Abstract: A total of 14.573 million fish fry and 96.32 million shrimp larvae were released across 31 locations into the coastal waters off Guangdong, China, in 2010. The released fish and shrimp were sampled through a combination of market and fishing log‐book surveys. The combined fishery production reached 362 868 kg. The input–output ratio was 1:5.99 for released fish (over 3 years) and 1:11.01 for released shrimp (over 2 years). The average increase in income was 721 RMB per capita. Approximately 240 thousand fish (after 3 years) and 1.2 million shrimp (after 2 years) survived to sexual maturity and could contribute to the spawning stock. The stockings were approximately one‐seventh of the fish and one‐half of the shrimp stocking carrying capacities, respectively. Based on these results, the intensity of stocking could be increased. Stocking and recapture strategies should be adjusted to align with the optimal stocking carrying capacity determined from this study.